Substance Abuse in Teenage Pregnancies – The Current Role of Psycho-Education - Natasha Singh; Prutha Desai; Alexandra Minseo Kim; Shabbir Amanullah (BJPsych Open, 2025)
Aims: To explore the current availability of psycho-education as a primary prevention against substance misuse in unplanned pregnancies for adolescents in the UK. It was noted that 80% of young adults registered with drugs and alcohol services started misusing substances under the age of 15 years. This poses an apparent risk of young mothers who are abusing drugs to have unplanned pregnancies. Moreover, pregnancies occurring sooner than desired are associated with higher risks to the health of the fetus because of delayed recognition. A study from the United States shows that women who reported using hard drugs, cannabis or smoking cigarettes at age 18 had an increased likelihood of risk behaviours and subsequent unplanned pregnancies.